2016
DOI: 10.2500/aap.2016.37.3951
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and risk of breakthrough varicella infection in children

Abstract: Background:We recently reported a more rapid waning of vaccine-induced humoral immunity (measles vaccine)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
(38 reference statements)
1
13
0
Order By: Relevance
“…Overall, the study results are consistent with the current literature suggesting the association of asthma with the risk of a broad range of infections. For example, our group has reported the increased risk of pertussis , breakthrough varicella infection , Streptococcus pyogenes infection , herpes zoster , community‐acquired E. coli blood stream infection and appendicitis , and these results were supported by the work of others . Again, these study results suggest that asthma poses increased risk of a broad range of infections from respiratory, urinary and gastrointestinal infections.…”
supporting
confidence: 72%
“…Overall, the study results are consistent with the current literature suggesting the association of asthma with the risk of a broad range of infections. For example, our group has reported the increased risk of pertussis , breakthrough varicella infection , Streptococcus pyogenes infection , herpes zoster , community‐acquired E. coli blood stream infection and appendicitis , and these results were supported by the work of others . Again, these study results suggest that asthma poses increased risk of a broad range of infections from respiratory, urinary and gastrointestinal infections.…”
supporting
confidence: 72%
“…However, the fact that early varicella infection is associated with the incidence of herpes zoster in immunocompetent children has been accepted by most researchers [6171924]. Furthermore, the incidence of herpes zoster is known to be high in children without immunodeficiency but who have chronic diseases such as asthma or diabetes [252627]. One Korean study reported that the incidence of herpes zoster in children have increased since the mid-1990s, when the varicella vaccine was introduced, and that the median age of incidence is 9.9 years [11].…”
Section: Discussionmentioning
confidence: 99%
“…Control of asthma through interventions (e.g., inhaled corticosteroid [ICS]) improved airway inflammation, respiratory symptoms, asthma exacerbations, rescue medication use, quality of life, and bronchial responsiveness, suggesting that early ICS intervention might have beneficial effects for those at risk of poor long-term asthma outcomes (1719). In addition, the recent literature suggests that childhood asthma poses numerous health threats through asthma-associated infectious and inflammatory disease comorbidities (AIICs) (2031). Both children and adults with asthma are at an increased risk of serious respiratory infections [e.g., pneumococcal pneumonia or invasive pneumococcal diseases (2022), pertussis (23), and common upper respiratory infections (e.g., otitis media and strep infection) (2426).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative asthma criteria, Predetermined Asthma Criteria (PAC) (Table 2-1) which is conceptually similar to the Canadian Thoracic Society criteria, consists of (1) airflow obstruction, (2) reversibility and variability of airflow obstruction (e.g., recurrent wheezing with respiratory symptoms), and (3) no evidence of alternative diagnosis. Its usefulness in detection of asthma has been proven in numerous asthma epidemiology (20, 2331, 4047). Also Asthma Predictive Index (API) (Table 2-2) which was developed to identify young children at risk of developing asthma can also be considered as feasibility of application of API to retrospective studies has been recently established (48, 49).…”
Section: Introductionmentioning
confidence: 99%